Dicentrarchus labrax - Çiçek, Erdoğan; Fricke, Ronald; Sungur, Sevil; Çapar, Osman Bahadir; Golani, Daniel (Zenodo, 2023)
Dicentrarchus labrax (Linnaeus, 1758) [N]—European seabass; Labrak halak Taxonomy. Original description: Perca labrax Linnaeus, 1758: 290 [Southern Europe, Mediterranean Sea; syntypes: BMNH 1853.11.12.1 (1, skin)].— Israel synonyms: Morone labrax (Linnaeus, 1758).—Revisions: None.—Illustration: Tortonese in Whitehead et al. (1986: 794, fig.). Status in Israel. First record in freshwater from Israel by Yashouv (1969); confirmed by Goren & Ortal (1999), Golani & Mires (2000).—Israel material: HUJ. Distribution and habitat. Distribution in Israel: Mediterranean watersheds.—Distribution in River Basin: 1- Western Basin, 2-Dead Sea Basin.—General distribution: Western Baltic Sea; North Sea; Mediterranean Sea; Sea of Marmara; Black Sea; Eastern Atlantic: Norway and Iceland south to Senegal, including Madeira; Red Sea: Gulf of Suez (Mediterranean Sea immigrant).—Distribution in Ecoregion: 436-Coastal Levant, 438- Jordan River.— Habitat: This species is pelagic, near shore, and sometimes in lagoons and estuaries. It spawns at sea. Freshwater, brackish, marine. Economic importance. Commercially important. Conservation. Conservation status in Israel: Unknown.—IUCN: LC (IUCN 2023).—Threats: No major threats known.—Low sensitivity to human activities.—Not considered a keystone species.—Decline status: Unknown.— Low priority for conservation action. Conservation. This species is naturally found in Mediterranean watersheds. It is introduced to inland water systems. Published as part of Çiçek, Erdoğan, Fricke, Ronald, Sungur, Sevil, Çapar, Osman Bahadir & Golani, Daniel, 2023, Freshwater fishes of Israel; a revised and updated annotated checklist- 2023, pp. 451-484 in Zootaxa 5369 (4) on pages 474-475, DOI:10.11646/zootaxa.5369.4.1, http://zenodo.org/record/10146651